Nutrition in congenital heart disease. (Colombia Medica, 2007)
Pediatric heart disease classification, in congenital and acquired, restrictive and non-restrictive, cyanotic and non-cyanotic, surgical and non-surgical and acute and chronic, is useful to determine its impact on child’s nutritional status. The nutritional management of CHD children is changing, due to liquid restriction high calorie requirements and high prevalence of food intolerance. Despite this, a close follow-up and several creative feeding methods, are essential to obtain optimal medical, nutritional and psychosocial results.